Fluorination and its Effects on Electrocatalysts for Low‐Temperature Fuel Cells. Issue 15 (9th March 2023) - Chatenet, Marian; Berthon‐Fabry, Sandrine; Ahmad, Yasser; Guérin, Katia; Colin, Marie; Farhat, Hani; Frezet, Lawrence; Zhang, Gaixia; Dubois, Marc
Abstract: The benefits of covalent grafting of fluorine atoms onto carbonaceous materials are described for the design of new electrocatalysts for low‐temperature fuel cells. In order to obtain the best results, the fluorination conditions must be carefully chosen according to the physicochemical properties of the starting materials (specific surface area, pore size distribution, crystallinity, and doping). By describing the main fluorination routes, the article aims to help in the choice of efficient treatment conditions. The effects of fluorination on the performance of the platinum group metal (PGM)‐based catalyst and the non‐PGM‐based electrocatalyst are discussed. Finally, future research prospects and technical challenges of fluorination for fuel cells are proposed. Abstract : The advantages of covalently grafting fluorine atoms onto carbon‐based materials for the development of novel electrocatalysts for low‐temperature fuel cells are discussed in this article. The various fluorination methods and how they affect both platinum‐group metal (PGM) and non‐PGM catalyst performance are discussed. The discussion concludes with future research potential and technological difficulties.